Employee attitudes leads to the level of employee affective commitment / Junaida Ismail...[et al.] - Ismail, Junaida; Ladisma @ Awis, Mahadir; Mohd Amin, Siti Hajjar (2010)
Commitment is a manifestation of individual owns self and reflect values standard that are basic to an individual’s existence as a person. Commitment a closely associate with the attitudes of employee. Attitudes can be described as an evaluative statements or judgments concerning objects, people or events (Robbins & Judges, 2007), it’s because employee’s attitudes can reflect from the emotion on attachment to the particular organization and amplify employee’s productivity. This study particularly examines the importance employee attitudes that can be revealing from the aspect on affective commitment. Affective commitment is one part of the organizational commitment. Which is organizational commitment can be classified into three (3) aspects which are affective commitment, continuance commitment and normative commitment. The objective of this study is to measure the employee attitudes among non academic in UiTM Kedah by using the affective commitment. 100 samples were selected involved eight departments in UiTM Kedah. The results show affective commitment is positively influence the employee commitment. In conclusion, it is hoped that this paper will give some insight to promote the importance on affective commitment among the government servant especially the non-academic staff in UiTM Kedah in order to increase their level of efficiency concerning the attitudes stability towards their own organization attached.